Unveiling professional and personal preferences of early career dentists during first year of employment at the Thai dental public sector: a one-year cross-sectional study - Tanit Arunratanothai; Ravisorn Booncharoen; Sirapop Suwankomolkul; Nareudee Limpuangthip (BMC, 2023)
Abstract Background Despite the implementation of various government policies to retain Thai dentists in public sector, a high turnover rate among early career dentists has persisted for decades. This study aims to explore factors relating to early career dentists' choice of the public sector as their preferred workplace and decisions relating to staying, resigning, or relocating from the workplace after one-year employment. Methods A one-year cross-sectional survey was conducted among Thai early career dentists who began working in 2020 using two sets of online questionnaires. The first survey assessed factors influencing dentists' decision to choose the public sector as their preferred workplace at the beginning of the year. The second survey investigated factors influencing dentists' decision to stay, resign, or relocate from the same workplace at one-year after employment. Descriptive statistics and multivariable binary logistic regression were used for data analysis. Results A total of 198 early career dentists completed the online survey questionnaire at the starting point (December 2020-January 2021), and 186 dentists completed the one-year employment questionnaire. The living environment and provided amenities and facilities were the most influential factors in their decision to choose and remain in the public sector. Conversely, their attitude toward unrelated job descriptions and an increased opportunity to pursue postgraduate studies were the most relevant factors when deciding to relocate to a new workplace. Factors such as delayed authority in bureaucracy, hometown location, and being in relationship status were the most significant contributors to resignation from the public sector. Conclusions The major factors influencing dentists' choice and retention in the public sector include the living environment, supportive supervisors and colleagues, and the availability of opportunities for further postgraduate education. Meanwhile, factors impacting retention after one year of work are related to hometown location and the bureaucracy system. Collaborations among ministries, tailored to each local community's specific requirements, may enhance dentists' retention in public sectors.